FLUTTER SPEED LIMITS OF SUBSONIC WINGS (Journal of Engineering, 2012)
Flutter is a phenomenon resulting from the interaction between aerodynamic and structural dynamic forces and may lead to a destructive instability. The aerodynamic forces on an oscillating airfoil combination of two independent degrees of freedom have been determined. The problem resolves itself into the solution of certain definite integrals, which have been identified as Theodorsen functions. The theory, being based on potential flow and the Kutta condition, is fundamentally equivalent to the conventional wing-ection theory relating to the steady case. The mechanism of aerodynamic instability has been analyzed in detail. An exact solution, involving potential flow and the adoption of the Kutta condition, has been analyzed in detail. The solution is of a simple form and is expressed by means of an auxiliary parameter K. The use of finite element modeling technique and unsteady aerodynamic modeling with the V-G method for flutter speed prediction was used on a fixed rectangular and tapered wing to determine the flutter speed boundaries. To build the wing the Ansys 5.4 program was used and the extract values were substituted in the Matlab program which is designed to determine the flutter speed and then predicted the various effects on flutter speed. The program gave us approximately identical results to the results of the referred researches. The following wing design parameters were investigated skin shell thickness, material properties, cross section area for beams, and changing altitude. Results of these calculations indicate that structural mode shape variation plays a significant role in the determination of wing flutter boundary.